Comparison of Commercial and Business Aviation - Šourek, David; Pazourek, Michal (Kaunas University of Technology, 2017)
The business aviation is on increase not only in the Czech Republic but quite often is not clear the difference between commercial aviation and business aviation. Commercial aviation together with business aviation is a part of the civil aviation. These both types of aviation seem to be very similar at first sight but there are many differences between them. The definition of commercial and business aviation is mentioned at the start of this paper. In the next part, the typical types of operations for commercial and business aviation are described. Based on this description, the differences between commercial and business aviation are evaluated. It is shown there are very big differences between e. g. aircraft interiors, a number of destinations etc. and that the business aviation is very specific part of civil aviation.
Porovnání obchodního a podnikového letectví
Keywords: business aviation; commercial aviation; podnikové letectví; obchodní letectví